Organisation of primary health care systems in low- and middle-income countries: review of evidence on what works and why in the Asia-Pacific region. (16th August 2019) - Dodd, Rebecca; Palagyi, Anna; Jan, Stephen; Abdel-All, Marwa; Nambiar, Devaki; Madhira, Pavitra; Balane, Christine; Tian, Maoyi; Joshi, Rohina; Abimbola, Seye; Peiris, David
Abstract : Introduction: This paper synthesises evidence on the organisation of primary health care (PHC) service delivery in low-income and middle-income countries (LMICs) in the Asia Pacific and identifies evidence of effective approaches and pathways of impact in this region. Methods: We developed a conceptual framework describing key inputs and outcomes of PHC as the basis of a systematic review. We searched exclusively for intervention studies from LMICs of the Asia-Pacific region in an effort to identify 'what works' to improve the coverage, quality, efficiency, equity and responsiveness of PHC. We conducted a narrative synthesis to identify key characteristics of successful interventions. Results: From an initial list of 3001 articles, we selected 153 for full-text review and included 111. We found evidence on the impact of non-physician health workers (NPHWs) on coverage and quality of care, though better integration with other PHC services is needed. Community-based services are most effective when well integrated through functional referral systems and supportive supervision arrangements, and have a reliable supply of medicines. Many studies point to the importance of community engagement in improving service demand. Few studies adopted a 'systems' lens or adequately considered long-term costs or implementation challenges. Conclusion: Based on our findings, we suggest five areas where more practical knowledge and guidance is needed to support PHC systems strengthening: (1) NPHW workforce development; (2) integrating non-communicable disease prevention and control into the basic package of care; (3) building managerial capacity; (4) institutionalising community engagement; (5) modernising PHC information systems.